2017
DOI: 10.1111/fwb.12899
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in phytoplankton beta diversity patterns and metacommunity structures across subtropical reservoirs

Abstract: Summary Analysing the beta diversity components and spatial patterns of species distribution may provide key insights into how local communities respond to human‐induced environmental changes. Indeed, analysing temporal variation in spatial patterns of species distribution may reveal trends of biotic homogenisation and its likely causes. We used an eight‐year phytoplankton data set generated from to 17 reservoirs in Brazil to analyse the temporal variability in beta diversity and its turnover and nestedness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 75 publications
(118 reference statements)
3
25
1
3
Order By: Relevance
“…In this case, our results indicated that environmental and spatial dynamics were temporally structured, directly influencing RFG biomass. Such assessments are in line with other studies that corroborate that the metacommunity organisation varies over time (Wojciechowski et al ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this case, our results indicated that environmental and spatial dynamics were temporally structured, directly influencing RFG biomass. Such assessments are in line with other studies that corroborate that the metacommunity organisation varies over time (Wojciechowski et al ).…”
Section: Discussionsupporting
confidence: 92%
“…The spatial signal has already been strongly related to the dispersal capacity of organisms and to the spatial scale considered (Padial et al ; Santos et al ; Moresco et al ; Chaparro et al ). The fact that the spatial component contributes more to community variation suggests that the distance between lakes was important for the structuring of the flagellate mixotrophic metacommunity (suggesting that it is in accordance with the mass‐effects model) and that this influence may change over time (Wojciechowski et al ). However, we emphasise that this ‘spatial signal’ may be related to spatially structured abiotic or biotic variables, or yet, to unmeasured variables (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…Anti-nested patterns dominated by species replacements have appeared frequently in freshwater studies employing the Leibold and Mikkelson (2002) analysis framework (Bried et al 2015, Heino et al 2015, Dallas et al 2016, Erös et al 2017, Wojciechowski et al 2017), but most of these studies involve dispersal-connected situations, i.e. metacommunities.…”
Section: Lack Of Nestedness and Checkerboardsmentioning
confidence: 99%
“…Dams can reduce the hydrological connectivity among neighbouring habitats or, inversely, enhance the connectivity, allowing the dispersal of species beyond their natural range (Havel, Lee, & Vander Zanden, ; Johnson, Olden, & Vander Zanden, ). For example, reservoir construction may contribute to biotic homogenisation by reducing the heterogeneity or complexity of habitats and circumventing natural biogeographical filters (Petsch, ; Rahel, ; Simões, Dias, et al., ; Vitule, Skóra, & Abilhoa, ) and through increasing the primary productivity (Wojciechowski, Heino, Bini, & Padial, ). Consequently, it is also expected that such an impact of dams affects the β‐diversity in downstream river–floodplain systems (Bozelli, Thomaz, Padial, Lopes, & Bini, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, reservoir construction may contribute to biotic homogenisation by reducing the heterogeneity or complexity of habitats and circumventing natural biogeographical filters (Petsch, 2016;Rahel, 2002;Simões, Dias, et al, 2013;Vitule, Sk ora, & Abilhoa, 2012) and through increasing the primary productivity (Wojciechowski, Heino, Bini, & Padial, 2017). Consequently, it is also expected that such an impact of dams affects the b-diversity in downstream river-floodplain systems (Bozelli, Thomaz, Padial, Lopes, & Bini, 2015).…”
Section: Introductionmentioning
confidence: 99%